2003
DOI: 10.4269/ajtmh.2003.69.411
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Household-Based Flocculant-Disinfectant Drinking Water Treatment for Diarrhea Prevention in Rural Guatemala

Abstract: We conducted a study to determine if use of a new flocculant-disinfectant home water treatment reduced diarrhea. We randomly assigned 492 rural Guatemalan households to five different water treatment groups: flocculantdisinfectant, flocculant-disinfectant plus a customized vessel, bleach, bleach plus a vessel, and control. During one year of observation, residents of control households had 4.31 episodes of diarrhea per 100 person-weeks, whereas the incidence of diarrhea was 24% lower among residents of househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 10 publications
4
123
2
Order By: Relevance
“…Other studies, however, have not found such a large advantage for chlorine. A study in Guatemala that evaluated sodium hypochlorite (bleach) and PUR demonstrated no significant difference between the two technologies, both of which reduced diarrhea by ~25% (28). Precise rankings of POU-based disease reduction are difficult to ascertain, as we describe in the following paragraph, but more qualitative conclusions are possible.…”
Section: A Shift To Household Technologiesmentioning
confidence: 88%
“…Other studies, however, have not found such a large advantage for chlorine. A study in Guatemala that evaluated sodium hypochlorite (bleach) and PUR demonstrated no significant difference between the two technologies, both of which reduced diarrhea by ~25% (28). Precise rankings of POU-based disease reduction are difficult to ascertain, as we describe in the following paragraph, but more qualitative conclusions are possible.…”
Section: A Shift To Household Technologiesmentioning
confidence: 88%
“…The lack of health impact in the context of successful treatment of stored drinking water was not consistent with results of previous studies of other chlorine-based, point-of-use water treatment interventions. 7,9,[12][13][14][15][16] There are several possible explanations for the observed lack of health impact. First, it is possible that disinfected stored water does not prevent diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5]7,9,[12][13][14][15][16] A recent meta-epidemiological study assessed the evidence for bias in controlled trials due to lack of blinding 34 and, although the review did not specifically assess point-ofuse water treatment intervention trials, it did estimate that trials with subjective outcomes exaggerated the actual effect of those outcomes by approximately 25%. Thus, even if the pooled estimate of the effect of household water treatment were adjusted by this factor of 25%, the protective effect would still be greater than 30%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Evidence on the positive effect of point-of-use treatment on water quality, and significant reductions in diarrheal diseases among its users, exists. [4][5][6][7][8][9][10][11] The usage of chlorine products has been described as one effective and easy-to-use means of water disinfection. Likewise, the protective effect of solar-disinfected water against cholera infections in small children has been shown and could serve as an alternative point-of-use treatment method.…”
Section: Introductionmentioning
confidence: 99%